Rejection, Acceptance, and Support: Experiences of LGBTQIA+ College Students in a Catholic School - Fernando, Daniel; Cabardo, Christopher (Technium Social Sciences Journal, 2024)
Gender is socially constructed beliefs perceived or ascribed to the sex identity of the person. Thus, this study explored, described, and interpreted the social experiences of LGBTQIA+ college students in a Catholic School. This study employed a descriptive qualitative research design. Hence, it helped to obtain a rich narrative concerning the social experiences of this group of students studying in a private Catholic school. Moreover, this paper came up with six participants determined through purposive sampling and set inclusion criteria. It employed the semi-structured in-depth interview. Also, this study utilized Lichtman’s 3Cs in analyzing the narratives of the participants. This study revealed that LGBTQIA+ college students experienced bullying and discrimination during their basic education years when they were trying to come out as who they were. Alongside the experience of coming out, they felt that they were not accepted by their father as members of the social group since they would be vulnerable to any form of humiliation. However, being a student in a Catholic school, they felt that they were accepted and welcomed. Likewise, they never experienced what happened during their high school years. Hence, the findings may serve as an eye-opener for many about the social experiences of this minority to elicit the practice of gender sensitivity and equality.